Manajemen Pengelolaan Kelas Masa Pandemi di SD Ta’miriyah Surabaya - Bahroin Budiya (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2021)
. In teaching and learning activities, there are two things that determine whether or not a teaching and learning process is carried out, namely class management and managing itself. The two things are interdependent. Students can study well, in a reasonable atmosphere without pressure and in conditions that stimulate learning. To create an atmosphere that fosters passion for learning, improves student learning achievement, and allows teachers to better guide students in learning, adequate classroom management is needed. Therefore, researchers are interested in taking the title of research on the effectiveness of classroom management in increasing learning activities at SD Ta'miriyah Surabaya. This study and discussion aims to: 1) Describe effective classroom management in terms of room management in increasing learning activities. 2) Describe effective classroom management in terms of student management in increasing Islamic Education learning activities. 3) Describe the inhibiting factors in class management to increase learning activities. In the current pandemic era, many schools have closed, causing learning through courage or learning from home. Therefore, the researchers took the title regarding classroom management during this pandemic